Reduction of Mature B Cells and Immunoglobulins Results in Increased Trabecular Bone. (30th August 2022) - Lagerquist, Marie K.; Gupta, Priti; Sehic, Edina; Horkeby, Karin L.; Scheffler, Julia M.; Nordqvist, Jauquline; Lawenius, Lina; Islander, Ulrika; Corciulo, Carmen; Henning, Petra; Carlsten, Hans; Engdahl, Cecilia
ABSTRACT: Inflammation has a significant effect on bone remodeling and can result in bone loss via increased stimulation of osteoclasts. Activated immunoglobulins, especially autoantibodies, can increase osteoclastogenesis and are associated with pathological bone loss. Whether immunoglobulins and mature B lymphocytes are important for general bone architecture has not been completely determined. Here we demonstrate, using a transgenic mouse model, that reduction of mature B cells and immunoglobulins leads to increased trabecular bone mass compared to wild‐type (WT) littermate controls. This bone effect is associated with a decrease in the number of osteoclasts and reduced bone resorption, despite decreased expression of osteoprotegerin. We also demonstrate that the reduction of mature B cells and immunoglobulins do not prevent bone loss caused by estrogen deficiency or arthritis compared to WT littermate controls. In conclusion, the reduction of mature B cells and immunoglobulins results in disturbed regulation of trabecular bone turnover in healthy conditions but is dispensable for pathological bone loss. © 2022 The Authors. JBMR Plus published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research.